Obtenção e análise de filmes finos de CdS e TiO2 para uso em células solares fotovoltaicas - Sousa, Charllys Barros Andrade (2010)
This work is dedicated to the deposition and characterization of thin films of cadmium sulfide and titanium dioxide for application in photovoltaic solar cells. Each film is deposited by a different process. The reagent TiO2 brand Vetec, was mixed with hydrochloric acid in aqueous solution forming a dispersion. This dispersion is spread on the glass substrate and then heated with a plate heater. After the deposit, were made SEM and EDX of the films. In order to prepare CdS a more complex process called chemical bath deposition was required, made of a mixture of reagents with the substrate immersed in it. Chemical reactions occurred which result was the formation of CdS, which occurs across the surface of the container and the substrate immersed in the solution. The same characterizations were carried out on TiO2 in CdS, showed in both good uniformity, was also observed that the films showed good adhesion to the substrate. In order to prove that films are applicable for photovoltaic energy conversion, a prototype of a solar photovoltaic cell was prepared, which was placed in contact with a type of light for measuring electrical parameters like the electric current and potential difference. We also measured the same parameters in the dark, for comparison of results and to prove power generation in contact with the light. The research tests provides evidence that films showed the photoelectric effect, therefore, applicable in photovoltaic solar cells.